Sistem Pendukung Keputusan Pemilihan Siswa Penerima Bantuan Program Indonesia Pintar Menggunakan Metode Weighted Product Berbasis Website - Wildan Wahyudi; Dwi Bayu Rendro (KOLONI, 2023)
The Smart Indonesia Program (PIP) is a government program that aims to help reduce costs for school-aged children who come from poor/vulnerable to poor families. The method of selecting recipients of PIP assistance carried out at SDN Sindangkarya 2 allows for human error to occur, causing the selection to not be objective. So it is necessary to build a decision support system using the Weighted Product method as an alternative solution, so that the selection process is on target and does not take up a lot of time. This system was designed using the Unified Modeling Language which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. To develop this system using the Prototype method. This system was tested using the black box testing method. The process for selecting students who receive the Smart Indonesia Program consists of five criteria, namely report card grades, parent's income, number of parent's dependents, condition of being orphaned and possession of a Certificate of Inadequacy (SKTM) or Prosperous Family Card (KKS). This research produces a Decision Support System that can select students who receive assistance from the Smart Indonesia Program on target and minimize selection time. Keywords: Smart Indonesia Program, Decision Support System, Weighted Product